2015
DOI: 10.1371/journal.pone.0125320
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α, Matrix-Metalloproteinases 8 and 9 Levels in the Saliva Are Associated with Increased Hemoglobin A1c in Type 1 Diabetes Subjects

Abstract: BackgroundType 1 diabetes (T1D) is an autoimmune disease resulting in the targeted destruction of pancreatic β-cells and permanent loss of insulin production. Proper glucose management results in better clinical outcomes for T1D and provides a strong rationale to identify non-invasive biomarkers indicative or predictive of glycemic control. Therefore, we investigated the association of salivary inflammation with HbA1c in a T1D cohort.MethodsUnstimulated saliva was collected from 144 subjects with T1D at the US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
(35 reference statements)
1
11
0
2
Order By: Relevance
“…In the LEW.1AR1‐ iddm rat animal model of T1D, treatment with anti‐TNFα only in combination with anti‐ T‐cell receptor antibodies restored normoglycemia, normalized C‐peptide and increased beta‐cell proliferation 36 . Furthermore, T1D patients studies identified increased TNFα plasma concentration associated with higher HbA1c 37 and lower C‐peptide levels 38 . In accordance, we found TNFα‐dominant T MEM responses especially at long‐term T1D stage.…”
Section: Discussionsupporting
confidence: 80%
“…In the LEW.1AR1‐ iddm rat animal model of T1D, treatment with anti‐TNFα only in combination with anti‐ T‐cell receptor antibodies restored normoglycemia, normalized C‐peptide and increased beta‐cell proliferation 36 . Furthermore, T1D patients studies identified increased TNFα plasma concentration associated with higher HbA1c 37 and lower C‐peptide levels 38 . In accordance, we found TNFα‐dominant T MEM responses especially at long‐term T1D stage.…”
Section: Discussionsupporting
confidence: 80%
“…It has been shown that one of the factors regulating the production of VEGF is a pro-inflammatory cytokine TNF-α [43,53]. Kuehl et al [69] demonstrated a positive correlation between the concentration of the cytokine and HbA1c in the saliva of patients with T1D. This result would indicate a role of the cytokine in maintaining inflammation process in the course of the disease.…”
Section: Effects Of Continuous and Intermittent Exercise In Hypoxia Amentioning
confidence: 98%
“…Therefore, the observed in the present study tendency for TNF-α to decrease in response to hypoxia and interval exercise is an important finding. It has been shown that lower cytokine concentration can enhance angiogenesis [69,70], which can be beneficial in the organs, where the process is impaired (i. e., the skeletal muscles, the skin, the heart). ExC in hypoxia, on the other hand, caused an insignificant increase in TNF-α concentration.…”
Section: Effects Of Continuous and Intermittent Exercise In Hypoxia Amentioning
confidence: 99%
“…Отмечают повышенный уровень TNFα также у грызунов с аллоксановым и стрептозотоциновым диабетом [20]. Увеличение содержания TNFα обнаружи-вают не только в плазме крови и слюне больных СД [26], но также в различных тканях диабети-ческих крыс, в том числе в сетчатке глаза [23]. IL-1 подавляет продукцию инсулина β-клетками и стимулирует их апоптоз [28].…”
Section: Introductionunclassified
“…По-вышенное содержание IL-6 выявлено у больных СД 1 и СД 2 типа в плазме крови [15,22], а также в плазме крови мышей с аллоксановым диабетом [20]. У больных CД 1 типа содержание IL-6 кор-релировало с повышением уровня гликирован-ного гемоглобина [26].…”
Section: Introductionunclassified